Strategi Persatuan Penyandang Disabilitas dan Center Advokasi (PERPENCA) dalam Upaya Meningkatkan Kesejahteraan Sosial Penyandang Disabilitas di Kabupaten Jember - Manda Rosa Yanti; Muhammad Muhib Alwi (Sociocouns: Journal of Islamic Guidance and Counseling, 2026)
This study aims to identify and describe the strategies implemented by Perpenca in its efforts to improve the social welfare of persons with disabilities in Jember Regency. The method used is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results of the study indicate several obstacles to fulfilling the social welfare of persons with disabilities in Jember Regency, including: the persistence of negative stigma in society toward persons with disabilities, lack of support and acceptance from families, low self-esteem among persons with disabilities, limited human resource capacity among persons with disabilities, and a lack of awareness from both the public and government regarding the rights of persons with disabilities. Perpenca's strategies to improve the social welfare of persons with disabilities in Jember Regency include efforts to enhance resource and funding potentials, foster closeness and a sense of kinship among members with disabilities, and advocate for an accessible environment for persons with disabilities.